1988
DOI: 10.1063/1.341829
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and millimeter-wave power generation in silicon carbide avalanche devices

Abstract: Silicon carbide (SiC), due to its thermal and electronic properties, has long been considered an excellent device material for microwave and millimeter-wave power generation. Numerical simulations were performed to study the typical power generating capabilities of SiC impact avalanche transit-time (IMP A TT) diodes utilizing the recent experimental data available. Operating characteristics of double-drift IMPATT devices at 10, 35, 60 and 94 GHz are compared. Both pulsed mode and continuous-wave (cw) mode oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…We have fabricated various epoxy molds with normal and inverse diamond structures using the stereolithography method, and infiltrated the molds with a mixed slurry of SiC powder and polyester. SiC has the advantage of having a high dielectric constant of about 9.7 13 and good wave absorption ability 14–17 . These diamond structures were used to investigate the microwave absorption ability at the PBG frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…We have fabricated various epoxy molds with normal and inverse diamond structures using the stereolithography method, and infiltrated the molds with a mixed slurry of SiC powder and polyester. SiC has the advantage of having a high dielectric constant of about 9.7 13 and good wave absorption ability 14–17 . These diamond structures were used to investigate the microwave absorption ability at the PBG frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was concluded that the polytype 4H-SiC is most convenient for IMPATT diode fabrication due to the high and nearly isotropic electron mobility [6]. A number of numerical simulations [7,8] confirmed these estimations, but they did not give enough information to perform an accurate design of SiC IMPATT diodes, namely to calculate the optimal operating frequency of the structure with given doping profile. Indeed, the most important material parameter used in these numerical calculations, namely v S , was not determined accurately.…”
Section: Introductionmentioning
confidence: 88%
“…In this paper, numerical simulations based on a two-dimensional drift-diffusion transport model have been carried out for the 4H-SiC IMPATT diode with a high-low single drift structure. Table 1 shows the related material parameters of 4H-SiC used for device simulation at room temperature [27,28]. Electron and hole impact ionization rates are important parameters in determining the microwave output performance of the IMPATT diode.…”
Section: Materials Parameters and Simulation Methodsmentioning
confidence: 99%